A Case of "Late" Postsurgical Hypoparathyroidism. (31st May 2017) - Simões, Cesar Augusto; Costa, M. K.; Comerlato, L. B.; Ogusco, A. A.; Araújo Filho, V.; Dedivitis, R. A.; Cernea, C. R.
Abstract : Introduction . Postsurgical hypoparathyroidism normally occurs a short time after thyroid surgery in form of two clinical syndromes of different etiology and prognosis. The first is transitory and might spontaneously recover within a few weeks or months. The second is permanent and needs a definitive treatment. Only few cases of hypoparathyroidism clinically evident after many years from surgery have been reported. Case Report . A case of hypoparathyroidism clinically evident only three and a half years after surgery is reported. Our findings and review of a few cases reported by medical literature suggest the existence of a third form of postsurgical hypoparathyroidism, characterized by a late beginning.